FUTUH AL-ASRAR FI FADHAIL AT-TAHLIL WA AL-ADZKAR KARYA SYAIKH 'ABDULLAH BIN 'ABD AL-QAHHAR AL-JAWI AL-BANTANI - MUHAMMAD SHOHEH (Al Qalam, 2011)
Researches on Nusantara 'Ulama's works-including Banten 'Ulama's works-are scarcely found. if we seriously observe, a number of their works, especially old manuscripts, are more than those of having been researched, published, and informed to the wider sodery. This research aims at studying a Banten 'Ulama's work of the eighteenth century well-kept in the National Library of Indonesia entitled Futuh al-Asrar Ji Fadhail at-Tahlil wa al-Adzkar (FAFA). This manuscript is a copy of Syaikh 'Abdul Wahhab bin 'Abdul Ghani's work copied by Syaikh 'Abdullah bin 'Abd al-Qahhar al-Bantani in Mecca. This text is written to explain the virtue of tahlil and zikir in order that his tarekat disciples obtain an easiness in bringing himself nearer to the God, both when he is alone (sirr) and when he is in busy condition (Jahr). Meanwhile, the motive of Syaikh 'Abdullah bin 'Abd al-Qahhar al-Bantani in copying the text is to prove that the geneology of the Qadiriya Tarekat he inisiates is legal and is directly attached to the Sheikh of Qadiriya Tarekat in Madina when he studied in Mecca during three years. Through this legitimate license and inisiation, he then spread out this tarekat to the Sultan of Banten when he returned to his fatherland. It seems that the existence of this manuscript strengthen the evidence of the existence and the influence of Qadariya Tarekat in the Banten Sultanate in the eighteenth century. And this FAFTA text becomes the initial source to know the genesis of inisiation of Qadariya Tarekat which is obtained by Syaikh 'Abdullah bin 'Abd al-Qahhar al-Bantani who then became the reliant 'Ulama' of Sultan Abu Nasr Zainal Asyiqin (1753-1777). Key Words: Zikir, Qadiriya Tarekat, Banten Sultanate of the-18th century.